Six-legged robot capable of climbing various columnar objects - Aoyagi, Ryushi; Homma, Yoshihiro; Ito, Kazuyuki (2017 International Conference on Advanced Mechatronic Systems (ICAMechS), 2017)
The inspection and maintenance of large industrial plants is an important task expected to be performed by robots. In this research, we improve the mechanism of our previous flexible manipulator inspired by an octopus, and we develop a six-legged robot that can climb unknown columnar objects without sensing the shape of the objects.